A PfRH5-based vaccine is efficacious against heterologous strain blood-stage Plasmodium falciparum infection in aotus monkeys. - Douglas, A; Baldeviano, G; Lucas, C; Lugo-Roman, L; Crosnier, C; Bartholdson, S; Diouf, A; Miura, K; Lambert, L; Ventocilla, J; Leiva, K; Milne, K; et al. (Cell Press, 2015)
Antigenic diversity has posed a critical barrier to vaccine development against the pathogenic blood-stage infection of the human malaria parasite Plasmodium falciparum. To date, only strain-specific protection has been reported by trials of such vaccines in nonhuman primates. We recently showed that P. falciparum reticulocyte binding protein homolog 5 (PfRH5), a merozoite adhesin required for erythrocyte invasion, is highly susceptible to vaccine-inducible strain-transcending parasite-neutralizing antibody. In vivo efficacy of PfRH5-based vaccines has not previously been evaluated. Here, we demonstrate that PfRH5-based vaccines can protect Aotus monkeys against a virulent vaccine-heterologous P. falciparum challenge and show that such protection can be achieved by a human-compatible vaccine formulation. Protection was associated with anti-PfRH5 antibody concentration and in vitro parasite-neutralizing activity, supporting the use of this in vitro assay to predict the in vivo efficacy of future vaccine candidates. These data suggest that PfRH5-based vaccines have potential to achieve strain-transcending efficacy in humans.